Magnetic Field Dependence of Bipolar Magnetic Region Tilts on the Sun: Indication of Tilt Quenching - Jha B.K.; Karak B.B.; Mandal S.; Banerjee D. (My University, 2025)
The tilt of the bipolar magnetic region (BMR) is crucial in the Babcock-Leighton process for the generation of the poloidal magnetic field in the Sun. Based on the thin flux-tube model of the BMR formation, the tilt is believed to be caused by the Coriolis force acting on the rising flux tube of the strong toroidal magnetic field from the base of the convection zone. We analyze the magnetic field dependence of BMR tilts using the magnetograms of the Michelson Doppler Imager (1996-2011) and Helioseismic and Magnetic Imager (2010-2018). We observe that the distribution of the maximum magnetic field (B max) of BMRs is bimodal. Its first peak at the low field corresponds to BMRs that do not have sunspots as counterparts in the white-light images, whereas the second peak corresponds to sunspots as recorded in both type of images. We find that the slope of Joy's law (γ 0) initially increases slowly with the increase of B max. However, when B max 2 kG, γ 0 decreases. Scatter of the BMR tilt around Joy's law systematically decreases with the increase of B max. The decrease of observed γ 0 with B max provides a hint to a nonlinear tilt quenching in the Babcock-Leighton process. We finally discuss how our results may be used to make a connection with the thin flux-tube model. © 2020. The American Astronomical Society. All rights reserved..